Developing a patient portal for haematology patients requires involvement of all stakeholders and a customised design, tailored to the individual needs - Paul A. F. Geerts; Trudy van der Weijden; Pien G. M. Loeffen; Lise E. F. Janssen; Celine Almekinders; Tobias A. Wienhold; Gerard M. J. Bos (BMC Medical Informatics and Decision Making, 2019)
Abstract Background Electronic patient portals are increasingly being implemented, also in (haemato) oncology. However, portal usage is low and depends on user and provider engagement. We explored wishes, expectations and thoughts of patients with a haematologic malignancy and their physicians with regard to the electronic patient portal. Methods Based on insights from literature and a focus group discussion we built a 44-item questionnaire. This questionnaire was spread amongst patients with a haematologic malignancy at the outpatient clinic that was not yet exposed to patient portal facilities. Haematologists completed a questionnaire based on literature. Results Patients were interested in many different types of access to information and portal functionalities. However, their opinions varied about the provision of access to the portal to other people, the role of the physician, possibilities for communication via the portal and timing of access. The physicians acknowledged the relevance of the electronic patient portal, but had some worries about the patients’ autonomous information handling, organizational and technical issues. Patients frequently expressed to be open about the potential of the patient portal to orchestrate their care. Nevertheless, most physicians appreciated their supporting role towards the patient. Conclusions Patients and physicians appreciated the electronic patient portal. Both groups need to be involved in further portal development to improve engagement by meeting patients’ wishes, taking into account organizational and professional issues and managing expectations for both parties. To fit various patient profiles, portal design should be flexible and individualized. Further research should focus on the perceived added value and the impact on patient related outcome measures of portals.